Cardiac extracellular matrix metabolism: the roles of age and sex in collagen dynamics - Pandya, Kalyani (The University of Edinburgh, 2025)
Aging is a major risk factor for cardiovascular disease, making it crucial to understand physiological aging in the context of cardiovascular health. In the absence of pathology, aging leads to a reduction in cardiac output and increased heart rate variability, vascular stiffening, and cardiac fibrosis. This age-related cardiac fibrosis is characterized by increased myocardial stiffness due to excessive extracellular matrix (ECM) components like fibrillin and collagen. The mechanisms of cardiovascular aging are poorly understood, though inflammation, senescence, and oxidative stress are implicated. These factors result in adverse remodelling, collagen accumulation, cardiac stiffening, and reduced cardiac function. It remains unclear whether collagen accumulation stems from increased synthesis or reduced clearance. The overarching hypothesis of this project is that aging disrupts cardiac collagen metabolism, causing a decrease in collagen synthesis despite significant collagen accumulation, with higher rates of collagen synthesis and accumulation in males compared to females. Therefore, this thesis focuses on the effect of aging on cardiac collagen metabolism, particularly on collagen synthesis both in vivo and in vitro. It also examines the influence of sex on age-related collagen metabolism, as females are thought to be relatively protected from adverse collagen accumulation. This thesis employs a comprehensive approach to investigate the impact of aging and sex on collagen synthesis and metabolism across the heart through in vivo, in vitro, and ex vivo methods. A longitudinal Positron Emission Tomography (PET)/Computer Tomography (CT) imaging study in male (n=7-14) and female (n=7-14) Sprague-Dawley rats across five timepoints (1, 3, 6, 12, and 18 months) was carried out. Longitudinal characterization included survival analysis, body weight, and frailty measurements to assess age-related physiological changes. Cardiovascular health was evaluated using CT-derived cardiac volume measurements, tail-cuff plethysmography for blood pressure, and echocardiography at the final experimental timepoint. PET/CT imaging utilized cis-4-18F-fluoro-L-proline and trans-4-18F-fluoro-L-proline proline to measure unhydroxylated and hydroxylated collagen synthesis, respectively. Images were analysed using a cardiac template defining the four heart chambers. Additional groups were used for ex vivo tissue analysis included hydroxyproline, soluble, and insoluble assays for collagen content, advanced glycation end-product (AGEs) ELISA for crosslinking, and picrosirius red staining (PSR) staining for total collagen. In vitro studies examined age, sex, and drug effects of AGEs inhibitor ALT711/Algaebrium on cardiac fibroblast collagen synthesis and utilized radiotracer assays to assess collagen synthesis types. Characterisation of the preclinical model of aging in Sprague Dawley rats identified that survival between males and females showed no difference but that mortality increased in both sexes following a year. Similarly, all animals showed significantly increased frailty at 18 months, suggesting that our cohort had advancing biological age. Rats had healthy cardiovascular systems, with cardiac dimensions, blood pressure, and ejection fraction all within normal ranges, indicating no obvious cardiac dysfunction and suggesting we were measuring physiological cardiovascular aging. However, 18-month-old males showed significantly lower cardiac ejection fraction and end-diastolic volume compared to their female counterparts. This suggests that aging causes a reduction in cardiac function in males compared to females, although males remain physiologically healthy. Age and sex effects on cardiac collagen synthesis were studied in the left ventricle (LV) and right ventricle (RV). No sex differences were found in collagen synthesis types, and aging effects were assessed by collating male and female data. Hydroxylated collagen synthesis significantly declined in the LV at 12 months, as did unhydroxylated collagen synthesis. Histological analysis using PSR revealed peak total collagen in males at 12 months and in females at 6 months, with subsequent declines. Males showed increased soluble and insoluble collagen at 18 months compared to females. An AGEs crosslinking ELISA identified that males had a significant increase in crosslinking at 12 months which was not observed in female counterparts. In the RV, both hydroxylated and unhydroxylated collagen synthesis decreased with age, despite significant increases in total collagen at 6 and 12 months, followed by a decline at 18 months. These findings suggest that while collagen synthesis declines with age in both ventricles, males experience greater age-related collagen accumulation, contributing to increased cardiac stiffness and functional impairment compared to females. Similarly, the effect of age and sex was assessed on atrial cardiac collagen synthesis and deposition. Hydroxylated and unhydroxylated collagen synthesis were measured in the left atria (LA) and right atria (RA) with no significant sex difference observed in either chamber. In the LA, hydroxylated collagen synthesis was increased at 3 months and at 18 months. Interestingly, unhydroxylated collagen synthesis showed an increase at 3 months but no other significant changes with age in LA, suggesting that collagen synthesis in the LA remains stable with age. Within the RA we observed that hydroxylated collagen synthesis increased with aging and this was also observed with unhydroxylated collagen synthesis. Interestingly, no increased deposition of collagen was identified in histological analysis. In vitro, sex and age at the time of cell explantation appeared to have much clearer effects on collagen synthesis with male fibroblasts producing significantly more unhydroxylated collagen synthesis than female cardiac fibroblasts. We observed similar trends with hydroxylated collagen synthesis however this was not statistically significant. Aging was a key driver of both hydroxylated and unhydroxylated collagen synthesis with aged male cells having significantly higher uptake of both tracers. Interestingly, collagen deposition analysis suggested a disruption in collagen metabolism with aged cells producing significantly lower amounts of insoluble collagen compared to younger counterparts. Drug treatment with ALT711/Algaebrium showed no effect on collagen synthesis or deposition, potentially due to suboptimal dosage or that the drug only impacted directly the established crosslinking and no other part of the collagen cascade. In summary, this study found that aging significantly impacts cardiac collagen metabolism. For the first time collagen synthesis has been longitudinally assessed and evaluated in each cardiac chamber, revealing region specific dynamic changes. Males showed more pronounced age-related collagen accumulation and potential cardiac stiffness compared to females. In both the left and right ventricles, collagen synthesis had overall significant declines with aging. Contrastingly, in the atria, hydroxylated collagen synthesis increased significantly with age, but without corresponding increases in collagen deposition. All these findings point to a disruption in the homeostatic control of collagen turnover and suggest that synthesis is not directly responsible for collagen accumulation in aging, proving our hypothesis.
Keywords: Collagen Metabolism; Aging; Sex Differences; Cardiac Stiffness; Extracellular Matrix (ECM)